العناقيد الصناعية ودورها في خلق القيمة المشتركة في بيئة منظمات الاعمال بالجزائر-دراسة حالة المؤسسات الصيدلانية. - غربي, عادل (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2022)
الملخص: يشكل العمل المنفرد لمنظمات الأعمال خطرا على بقاءها واستمرارها بسبب التغير الحاصل في بيئة الأعمال نتيجة حدة المنافسة، وندرة الموارد، وقوة التجاذب الاقتصادي، مما أدى الى حتمية دخولها في تكتلات اقتصادية وتجمعات صناعية لإستغلال الاحتياجات المجتمعية والبيئية، وخلق قيمة مشتركة. وتهدف هذه الدراسة إلى تحليل واقع العناقيد الصناعية ودورها في خلق القيمة المشتركة في بيئة منظمات الأعمال بالجزائر، دراسة حالة المؤسسات الصيدلانية. وقد اعتمدت الدراسة على المنهج الوصفي التحليلي، بالإضافة إلى المقابلة، والاستبانة كأدوات لجمع البيانات والمعلومات، حيث وُزعت على عينة مكونة من 67 مؤسسة صيدلانية عامة ومختلطة وخاصة. كما استخدمت الدراسة الأدوات والأساليب الإحصائية لبرنامج الحزم الإحصائية SPSS، وبرنامج النمذجة بالمعادلات البنائية SEM. وقد خلصت إلى توافر إعتماد القيمة المشتركة، وأبعاد العناقيد الصناعية ضمن بيئة اعمال مؤسسات محل الدراسة بنسب متفاوتة، ووجود تأثير ايجابي لأبعاد العناقيد الصناعية على القيمة المشتركة ببعديها الاقتصادي والاجتماعي، كما كشفت بأن ثمة تباين في تأثير هذه الأبعاد على القيمة المشتركة، ووجود علاقة ارتباطيه موجبة بين العناقيد الصناعية وأبعادها بالقيمة المشتركة، كما بينت الدراسة أن معامل التحديد المفسر لعلاقة العناقيد الصناعية بالقيمة المشتركة بلغ 74.2%؛ أي أن كل تغيير قيمته 1% ينتج عنه تغير بقيمة 74.2 % للقيمة المشتركة، والباقي تفسره عوامل أخرى. Résumé : Due to the shift in the business climate brought on by fierce rivalry, a lack of resources, and the strength of economic attraction, business organizations' unilateral work poses a threat to the survival and continuity of these enterprises. This made its admission into economic blocs and industrial clusters to meet societal and environmental needs as well as to generate shared value inevitable. Through a case study of the pharmaceutical industry, this study attempts to investigate the existence of industrial clusters and their function in generating shared value in the environment of business organizations in Algeria. In addition to adopting an analytical descriptive method, the study also used interviews and questionnaires as data collection tools, to gather information from a sample of 67 public, mixed-use, and private pharmaceutical organizations. Additionally, the SPSS Statistical Package Program and the Structural Equations Modeling Program (SEM) were used. The study found that the institutions adopted the common value and the industrial cluster dimensions in varied degrees within the business environments of the institutions under study, and that these dimensions had a favorable impact on the common value in both its economic and social dimensions. Additionally, it showed that there is a difference in how these dimensions affect the common value and that there is a strong relationship between industrial clusters and their dimensions at the common value. That is, for every 1% change in value, the common value changes by 74.2%, with the remaining variation being explained by other factors.
أطروحة دكتوراه تخصص: .مقاولاتية في العلوم الاقتصادية و التجارية وعلوم التسيير
Keywords: خلق قيمة، خلق قيمة مشتركة، مسؤولية اجتماعية، عناقيد صناعية، منفعة اجتماعية، قطاع صيدلاني; value creation, shared value creation, social responsibility, industrial clusters, social benefit, pharmaceutical sector